ANALISIS STATISTIK PENGUJI KECENDERUNGAN POPULASI DAN VARIASI TIPE HABITAT BUAYA Crocodylusporosus DI DAERAH PASANG SURUT TELUK ARGUNI IRIAN JAYA - Hellen Kurniati (The East Java Biological Society, 2000)
The population ecology of saltwater (Crocodylusporosus) in Arguni Bay, Irian Jaya was studied during 19990-1998 period. In this study, the habitas were divided into five types (1. Dominant vegetation Nypafructicansand primary forest; 2.Dominant vegetations N. fructicans; 4.Mangrove; 5. Lake with dominate vegetation N. fructicans and mangrove, along the lake bank was covered by Barringtonia spp, Ficusspp and Callophylum spp, whereas almost at lake offshore was covered by lotus floating plant). Result of GLM statistical analysis showed there were no significant (p>0.05) interaction between habitat type and survey time, neither on the habitat type and time of survey. The Duncan test on habitat showed a grouping in three categories (A, AB, and B) in which habitat 5 was at first ranking. However, there was no grouping on time of survey. From this study it was concluded that mangrove habitat was essential for C.porosus life and used as a nursery ground.